Celebrity-fan engagement on Instagram and its influence on the perception of hijab culture among Muslim women in Malaysia - Tengku Mohd Azzman, Tengku Siti Aisha; A.Manaf, Aini Maznina (Penerbit UKM Press, 2019)
Celebrities who use Instagram can influence their female followers in many ways, for instance, in influencing their perceptions on body image, adoption of healthy eating lifestyles, and persuading them to purchase products or services endorsed by these celebrities. Accordingly, this study aims to examine the influence of celebrity-fan engagement on Instagram on hijab culture among Muslim women in Malaysia. A cross-sectional survey was conducted among female university students from the International Islamic University of Malaysia (N = 630). In order to participate in the study, respondents completed an online survey and are instructed to think about a favourite female Muslim celebrity they follow on Instagram while completing the research instrument. Results indicate that almost one-third of the most popular Muslim celebrities among females Instagram users are non-traditional celebrities (i.e. bloggers/vloggers, YouTube personalities and social media influencers). Furthermore, attitude homophily and parasocial interaction with said celebrity may significantly influence the likelihood that the celebrity’s profile will be visited, and the number of likes on their photos. Finally, after controlling for the respondents’ religious educational background, this study found that those who had positive attitude and behaviour towards the hijab, and perceived a higher degree of parasocial bond with Muslim celebrities on Instagram tended to have a more positive perception towards the hijab culture. The repercussions of these findings on the parasocial interaction theory, and the influence of celebrity-fan engagement on social media over hijab culture are discussed.